(untitled) (Research, Society and Development, 2020)
Cancer is the second leading cause of death in Brazil, its control and prevention represent one of the major public health problems in the country. Therefore, the study aimed to describe and analyze the knowledge of men about prostate cancer. This is a descriptive, exploratory study with a qualitative approach that was carried out in 3 Basic Health Units in the north of the city of Teresina-PI. The study was carried out with 18 men who were attended at the Basic Health Units through a semi-structured interview script. The study included men over 40 years of age with an active sexual life, who agreed to participate in the interview by signing the Free and Informed Consent Form. The exclusion criteria were: adolescents, adults under the age of 40, men who were prostatectomized or who had already suffered from prostate cancer and those who did not accept signing the Informed Consent Form. After collecting the data, they were analyzed using Minayo’s content analysis technique. The study showed the knowledge of men about prevention with speeches aimed mainly at performing preventive exams, as well as the embarrassment and fear of taking them. In addition to the attitudes and practices carried out by men for prevention, such as exams, healthy eating and physical activity practices. It is also possible to describe the importance of Nurses in raising awareness and attracting men to the Basic Health Units. It is considered that although men demonstrate knowledge about the forms of prevention, there is still resistance in carrying them out and Nursing should contribute to the men’s adherence to preventive practices.